BUSINESS COMMUNICATION STRATEGIES FOR DELIVERING MESSAGES TO BUILD CORPORATE IMAGE - Naylal Fithri; Indah Maslaha; Diana Wulandari; Muhammad Jamaluddin Affan; Muhammad Samir Hadromi (International Journal of Multidisciplinary Reseach, 2026)
Communication plays a very important role in human life, including in the business world. In the context of modern business, communication is no longer one-way but has become a two-way process involving interaction, openness, and trust-building between companies and society. This study aims to understand and explain message delivery strategies in business communication to build corporate image. The method used is descriptive qualitative with a literature study approach, utilizing various sources such as scientific journals, books, and relevant articles. The results show that media and technology play an important role in supporting the effectiveness of business communication, both internally and externally. Media such as email, social media, virtual meetings, and digital platforms help deliver information quickly, widely, and efficiently. However, technological developments also carry risks, such as the spread of inaccurate information, making good digital literacy necessary. In addition, the role of Public Relations (PR) and corporate communication is very important in building and maintaining corporate image and reputation through open, consistent, and strategic communication. Communication strategies are also key in dealing with crises by selecting appropriate media, crafting clear messages, and determining the right target audience. Overall, well-planned communication strategies supported by proper use of media and technology can help companies build a positive image and maintain their reputation in the digital era.